MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA TENTANG MEMBACA NYARING DENGAN METODE DEMONSTRASI SISWA KELAS III SD NEGERI NO. 071096 MANDREHE KECAMATAN MANDREHE KABUPATEN NIAS BARATSEMESTER I TAHUN PELAJARAN 2018/2019 - TOLONA GULO (JURNAL ILMIAH MAKSITEK, 2019)
Malaria is still one of the world's public health problems. Malaria can be influenced by the environment in which people live and include their knowledge, attitudes and actions. Public knowledge influences his actions, the better the level of community knowledge is expected the better the community's actions. The problem of community knowledge that is still lacking can be overcome by conducting counseling. This type of research is an analytic study using quasi-Experiment One Group Pre and Post Test Design.The purpose of this study was to determine the effect of counseling on parental knowledge about malaria prevention in Teladeh Hamlet Batu Jong-Jong Village Bahorok District 2016. The population in this study was 108 people with a sample of 45 people, the sample was obtained by quota sampling technique, data collection was done by using a questionnaire. Data processed using t dependent test. The results of the study obtained parental knowledge before being given counseling about malaria prevention had an average score of 5.7 with a minimum value of 0 and a maximum of 8.8 and parental knowledge after being given counseling about malaria prevention had an average score of 7.0 with a minimum score of 2 and a maximum of 9.2 there are differences in the average score of parental knowledge before and after counseling is 1.3. There is an influence of counseling on parental knowledge about malaria prevention in Teladeh Hamlet, Batu Jong-Jong Village, Bahorok District in 2016 with a p-value = 0,000.To the people of Dusun Teladeh it is better to apply knowledge about malaria prevention that has been known to reduce the risk of malaria and to the Bahorok Health Center Officers are expected to be able to disseminate information to other hamlets and to malaria endemic areas and motivate the community related to malaria prevention through counseling so that the community is willing and able to take malaria prevention measures.